2014
DOI: 10.1371/journal.pone.0098169
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Molecular Characteristics with Prognostic Significance in Diffuse Large B-Cell Lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive non-Hodgkin lymphoma with marked biologic heterogeneity. We analyzed 100 cases of DLBCL to evaluate the prognostic value of immunohistochemical markers derived from the gene expression profiling-defined cell origin signature, including MYC, BCL2, BCL6, and FOXP1 protein expression. We also investigated genetic alterations in BCL2, BCL6, MYC and FOXP1 using fluorescence in situ hybridization and assessed their prognostic significance. BCL6 rearrangements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…Specifically interesting in this scenario is that MYC translocations or MYC overexpression by other means is associated with poor survival, in particular in DLBCLs that also overexpress BCL2. 55,56 For such double-hit DLBCL patients, and also in DLBCL patients with just high MYC levels, SUMOi could be an attractive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically interesting in this scenario is that MYC translocations or MYC overexpression by other means is associated with poor survival, in particular in DLBCLs that also overexpress BCL2. 55,56 For such double-hit DLBCL patients, and also in DLBCL patients with just high MYC levels, SUMOi could be an attractive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BCL2 expression was significantly weaker than in control DLBCL samples ( P < 0.05). Bellas et al . demonstrated that expression of BCL2 and/or cMYC proteins led to significantly poorer overall survival in 100 patients with DLBCL ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BCL2 expression was significantly weaker than in control DLBCL samples (P < 0.05). Bellas et al 22 demonstrated that expression of BCL2 and/or cMYC proteins led to significantly poorer overall survival in 100 patients with DLBCL (P < 0.05). In RA patients with EBV + MTX-BLPD, low BCL2 expression in tumour cells may influence tumour regression even in non-GCB cell phenotype tumours, and result in better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…1317 Meanwhile, several other biomarkers, including CD5, p53, MYC expression, MYC/BCL2 co-expression, TP53 mutation, BCL2 , MYC rearrangement, and MYC / BCL2 double hit, have been implicated in mechanisms of disease and have been suggested as predictors of poor prognosis in DLBCL. 1824 Thus far, no large studies have explored the relationship between these high-risk pathologic features and the various types of BM involvement in DLBCL patients.…”
Section: Introductionmentioning
confidence: 99%